Sosialisasi Green Marketing dan Environmental Awareness bagi Kalangan Mahasiswa - Dhany Isnaeni Dharmawan (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2025)
This community service activity aims to enhance students' understanding and awareness of the green marketing concept and the importance of environmental preservation. Through socialization activities conducted via seminars, interactive workshops, educational module distribution, and group discussions, students of the Management Study Program at Universitas Serang Raya gained insights into sustainable and environmentally friendly marketing practices. Evaluation results indicate a significant increase in students' comprehension of green marketing concepts and environmental awareness. Students also demonstrated active participation, presented creative ideas, and showed commitment to applying sustainability principles within the campus and surrounding communities. This activity contributes to fostering pro-environmental behavior, strengthening students' capacity as agents of change, and supporting the educational institution's role in sustainable development. The results of this service are expected to be an initial step for integrating green marketing and environmental awareness education into the curriculum and ongoing campus activities.